Primary structure of gum arabic and its dynamics at oil/water interface. (1st December 2020) - Isobe, Noriyuki; Sagawa, Naoya; Ono, Yuko; Fujisawa, Shuji; Kimura, Satoshi; Kinoshita, Keigo; Miuchi, Takeshi; Iwata, Tadahisa; Isogai, Akira; Nishino, Masayuki; Deguchi, Shigeru
Highlights: Structure-interfacial property relationship of gum arabic (GA) is studied. Primary structure of GA is a disk-like star shaped nanoparticle. GA molecules adsorb onto oil surface in 2 steps. Emulsion stability is controlled by high-order molecular network. Abstract: Gum arabic (GA), an arabinogalactan-based gum, is a well-known powerful emulsifier. However, the poor stability of emulsion has often been pointed out. In order to clarify the origin, the structure-property relationship of GA, especially the interfacial property at oil/water interface, needs to be investigated. Here, we tried to correlate the primary structure with interfacial property at oil/water interface. A series of structural analyses by SEC-MALLS, SAXS, etc. showed that the primary structure of GA was a disk-like star shaped nanoparticle. The dynamic interfacial tension measurement showed that GA molecules adsorb onto oil surface in 2 steps: Firstly, the micron-aggregates of GA approach onto the oil surface, and then the aggregates are dissociated into nano-particles so that they cover the oil surface. Therefore, the emulsification and emulsion stability are controlled not by the property of the primary structure of GA but by the higher-order molecular network structure made of GA molecules.